Pengaruh Biaya Produksi Terhadap Harga Jual Ikan Nila Pada Balai Benih Ikan Lokal (BBIL) Di Desa Cukan Lipai Kecamatan Batang Alai Selatan Kabupaten Hulu Sungai Tengah - Azwar Saihani; Yulia Yulia (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2016)
This study aims (i) to know the effect of production costs on the selling price of tilapia, (ii) how the costs are spent on fish production in fish hatchery activities at the Local Fish Seed Center (LFSC) in Cukan Lipai Village, Batang Alai Selatan District, Hulu Sungai Tengah Regency. The method used is a case study, respondents in this study conducted interviews with employees of the Local Fish Seed Center (BBIL). The data analysis method used is multiple regression analysis, linear relationship equation between two or more independent variables so that the functional relationship between the dependent variable (Y) and the independent variable (XI, X2, Xn), X variable as the independent variable and Y variable as the dependent variable The results obtained a value (r²) of 0.374 which means that production costs have an influence on the selling price of 37.4%, in tilapia hatchery business in Cukan Lipai Village, Batang Alai Selatan District, Hulu Sungai Tengah Regency. The influence of variable (X) is the production cost of variable (Y) selling price is 37.4%, while the remaining 62.6% can be influenced by other variables not included in the equation model